Stateczność pełnego sprężystego walca przy dużych odkształceniach - ZŁATANOWA, Elena (Engineering Transactions, 1970)
Stability of a fully-elastic cylinder at large deformations The paper considers the stability of a full circular cylinder subjected to a finite stretching or compressing. It is assumed that the cylinder material is elastic and compressible with a completely arbitrary physical characteristic. The method of small deformations superposed on the initial finite deformations is used. After the linearization of the relationships for a small additional deformation a set or partial differential equations was obtained, which upon the decomposition of the functions sought for into a Fourier series became reduced to a set of ordinary differential equations. The general solution of this set of equations has been found. The boundary conditions were constructed for a load vertical to the front surfaces, and the lateral surfaces are not under load. The conditions of loss of stability are given corresponding to the above mentioned manner or loading.